A novel cobalt-free cathode with triple-conduction for proton-conducting solid oxide fuel cells with unprecedented performance. Issue 27 (22nd May 2019) - Xia, Yunpeng; Jin, Zongzi; Wang, Huiqiang; Gong, Zheng; Lv, Huanlin; Peng, Ranran; Liu, Wei; Bi, Lei
Abstract : Bi and Sn co-doped perovskite BaFe0.8− X Sn0.2 Bi X O3− δ materials have been designed and characterized as a series of new cathodes for proton-conducting solid oxide fuel cells (SOFCs), providing a new life for the traditional BaFeO3 -based cathodes. Abstract : Bi and Sn co-doped perovskite BaFe0.8− X Sn0.2 Bi X O3− δ materials have been designed and characterized as a series of new cathodes for proton-conducting solid oxide fuel cells (SOFCs), providing a new life for the traditional BaFeO3 -based cathodes. Proton uptake of the cathode increases significantly with bismuth-doping, favoring the application of Bi and Sn co-doped perovskite BaFe0.8− X Sn0.2 BiXO3− δ materials in proton-conducting SOFCs. The density functional theory (DFT) calculation also suggests that the bismuth-doping leads to a dramatic increase of hydration energy and acceleration of proton migration for the BFS material. The XPS results show that the oxygen reduction reaction (ORR) activity of the cathode is enhanced after bismuth is added, which is consistent with the experimental results of the power density of the single cell. The maximum power density of the single cells with the structure of NiO-BaZr0.1 Ce0.7 Y0.2 O3− δ |BaZr0.1 Ce0.7 Y0.2 O3− δ | BaFe0.5 Sn0.2 Bi0.3 O3− δ (BFSBi0.3 ) reached 1277 mW cm −2 at 700 °C, which is a record-high performance for proton-conducting SOFCs using cobalt-free cathodes, compared with previous reports. The outstanding fuel cell performance and good long term stability indicate that bismuth-doping is an effective way of promoting proton-conduction in traditional cathodes. This study opens a new door to the design of high performance cathodes for proton-conducting SOFCs.